RANCANG BANGUN MESIN PEMOTONG SERBA GUNA HEMAT ENERGI PENUNJANG PRODUKTIFITAS UKM KERUPUK - Akhmad Hafizh Ainur Rasyid; I Wayan Susila; Dewanto Dewanto; Dany Iman Santoso (Otopro, 2022)
Puli crackers are an SME business in Indonesia which has a fairly good protein composition and is usually used as souvenirs of Madura. The problems of most Indonesia’s SMEs are still using manual labour with makeshift equipment. and the assistant machines available in the market have a large capacity so they are not easy to use on a household scale with small electrical capacity. The development method used in the design of an energy-efficient general-purpose cutting machine is engineering design until test and evaluate prototype stage. The engine capacity is 1,065 gr/s at the 2nd or 3rd 24 V dimmer speed setting. The result of this design process is the selection of an electric motor driven machine that is adjusted to the required power with reduced direct transmission in order to be able to cut the cracker dough.